Radiative Effects of Water Clouds on Heat, Cloud Microphysical and Surface Rainfall Budgets Associated with Pre-Summer Torrential Rainfall - Jia Liu (Terrestrial, Atmospheric and Oceanic Sciences, 2014)

(untitled)
This study investigates thermal, cloud microphysical and surface-rainfall responses to the radiative effects of water clouds by analyzing two pairs of two-dimensional cloud-resolving model sensitivity experiments of a pre-summer heavy rainfall event. In the presence of the radiative effects of ice clouds, exclusion of the radiative effects of water clouds reduces the model domain mean rain rate through the mean hydrometeor increase, which is associated with the decreases in the melting of graupel and cloud ice caused by enhanced local atmospheric cooling. In the absence of the radiative effects of ice clouds, removal of the radiative effects of water clouds increases model domain mean rain rate via the enhancements in the mean net condensation and the mean hydrometeor loss. The enhanced mean net condensation and increased mean latent heat are related to the strengthened mean infrared radiative cooling in the lower troposphere. The increased mean hydrometeor loss associated with the reduction in the melting of graupel is caused by the enhanced local atmospheric cooling.